THE ROLE AND FUTURE PROSPECTS OF METAL MATRIX NANOCOMPOSITE MATERIALS IN THE AVIATION FIELD (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the role, scientific and practical aspects of metal-matrix nanocomposite materials (nanocomposits with metal materials) in the field of aviation. The high strength, lightness, heat resistance, and corrosion resistance of nanocomposits with metal materials make them superior to traditional metal alloys. Modern production technologies and new scientific approaches serve to increase the efficiency of nanocomposits with metal materials. According to the research results, the share of nanocomposits with metal materials in the aviation industry is significantly increasing and is expected to develop further in the future. Based on mathematical models, changes in strength and composition were assessed. The use of nanocomposits with metal materials serves to increase fuel efficiency, improve flight efficiency, and reduce the environmental impact of the aviation industry.